LUMINESCENCE SPECTROSCOPIC STUDY OF CR3+ IN BRAZILIAN TOPAZES FROM OURO PRETO - Tarashchan A.N.; Taran M.N.; Rager H.; Iwanuch W. (My University, 2006)
In this paper, the results of investigation of luminescent properties of topazes from Ouro Preto, Brazil are presented. It is established that all photoluminescence characteristics of variously colored topazes are due to three structurally non-equivalent Cr3+ centers isomorphically substituting Al3+ in the topaz structure and forming [CrO4F2]7-, [CrO4OH,F]7-, and [CrO4(OH)2]7- complexes. Kinetics of thermal annealing indicates different thermal stability of these centers. Less stable [CrO4OH, F]7-- and [CrO4(OH)2]7- complexes diminish in temperature range 950-1,100°C, accompanied by appearance of corundum phase. The most stable [CrO4F2]7- centers completely decay at 1,250°C and luminescence spectrum of product obtained becomes identical to that of Cr3+ in mullite indicating that topaz completely transforms to mullite. © Springer-Verlag 2005.
Keywords: CHROMIUM; LUMINESCENCE; PHASE-TRANSITIONS; TOPAZ